Analysis, design and development of web-based thesaurus manager prototype for Philippine medical thesaurus user components - Pacis, Rodney P. (2004)
The world of medicine is a vast repository of information designed to help the lives of people. And medical professionals in the Philippines which include doctors, nurses, medical technicians, etc. are exposed everyday to a variety of terms which are foreign in origin, making a Philippine Medical Thesaurus a welcome idea for it attempts to bridge certain language barriers and provide an increased understanding of medical terms.